Shared genetic influences on depression and menopause symptoms. Issue 6 (6th April 2023) - Meijsen, Joeri J.; Shen, Hanyang; Vemuri, Mytilee; Rasgon, Natalie L.; Koenen, Karestan C.; Duncan, Laramie E.
Abstract: Background: Women experience major depression and post-traumatic stress disorder (PTSD) approximately twice as often as men. Estrogen is thought to contribute to sex differences in these disorders, and reduced estrogen is also known to be a key driver of menopause symptoms such as hot flashes. Moreover, estrogen is used to treat menopause symptoms. In order to test for potential shared genetic influences between menopause symptoms and psychiatric disorders, we conducted a genome-wide association study (GWAS) of estrogen medication use (as a proxy for menopause symptoms) in the UK Biobank. Methods: The analysis included 232 993 women aged 39–71 in the UK Biobank. The outcome variable for genetic analyses was estrogen medication use, excluding women using hormonal contraceptives. Trans-ancestry GWAS meta-analyses were conducted along with genetic correlation analyses on the European ancestry GWAS results. Hormone usage was also tested for association with depression and PTSD. Results: GWAS of estrogen medication use (compared to non-use) identified a locus in the TACR3 gene, which was previously linked to hot flashes in menopause [top rs77322567, odds ratio (OR) = 0.78, p = 7.7 × 10 −15 ]. Genetic correlation analyses revealed shared genetic influences on menopause symptoms and depression ( rg = 0.231, s.e. = 0.055, p = 2.8 × 10 −5 ). Non-genetic analyses revealed higher psychiatric symptoms scores among women using estrogen medications. Conclusions: These results suggest that menopause symptoms have a complex genetic etiology which is partially shared with genetic influences on depression. Moreover, the TACR3 gene identified here has direct clinical relevance; antagonists for the neurokinin 3 receptor (coded for by TACR3 ) are effective treatments for hot flashes.